The Influence of the Use of Learning Media on the Activeness and Mathematics Learning Outcomes of Class II Students of Wates 02 Elementary School - Cahyani, Bella Galih; Oktavianingrum, Berliana Aurora; Hesvina, Eprilia; Saputri, Farica Dwi; Adilia, Tsabita Daffa; Tyas, Dewi Nilam (Lembaga Riset Mutiara Akbar, 2025)
This study aims to determine the effect of the use of concrete learning media, such as wall clocks, on the activeness and learning outcomes of grade II students at SD Negeri Wates 02. Media is one of the important components in the learning process, so this study aims to determine the effect of the use of concrete learning media, such as wall clocks, on the activity and learning outcomes of grade II students at SD Negeri Wates 02. This study uses a qualitative descriptive method with a sampling technique, namely the purposive sampling technique. Data collection was carried out through interviews, observations, and documentation which were then analyzed and interpreted. The results of observations and interviews showed that the use of these media was able to increase student activity, which was reflected in their involvement in observing, answering, and communicating. The implementation of this learning media is also directly proportional to the increase in student learning outcomes, as evidenced by the increase in daily test scores. These findings support the theory that concrete media has an effect on increasing student activity and learning outcomes at the elementary level, especially for materials that require visual understanding and direct experience.